USING INTERACTIVE APPROACH IN ENHANCING STUDENTS’ READING COMPREHENSION - Nurul Hayati; Usman Kasim; Asnawi Muslem (English Education Journal, 2020)
English is one of the compulsory subjects at schools in Indonesia, including at junior high schools. This study was conducted to investigate the effectiveness of implementing an interactive approach in teaching reading comprehension. It also investigated the students' responses toward the implementation of an interactive approach in teaching reading. The true-experimental design was carried out in this study along with the pretest and post-test. Two classes of the first-grade students of SMPIK Nurul Quran in Aceh Besar were chosen as the sample of the research with total population sampling technique. This sampling technique was employed because of the limited individuals to be randomized as samples. Each group consisted of 20 students for the experimental class and 20 students for the control class. The instruments used in this study were test and questionnaire. The data collected were analyzed using descriptive statistics through SPSS Version 20. The results show that the use of an interactive approach improved students’ reading scores and they also gave positive responses toward the use of interactive approach in teaching reading. Therefore, the alternate hypotheses of this research was accepted. It means that the implementation of interactive approach could increase students’ reading scores significantly as compared with the students who were taught by using the bottom-up approach. The students also had positive responses to the implementation of interactive approach during teaching and learning reading comprehension. It can be concluded that interactive approach is one of the effective approach for teaching reading comprehension.